Flow-excited acoustic pulsations in ducts with closed side branches - MEISSNER, M. (Archives of Acoustics, 1997)
In flow ducts with closed side branches strong acoustic pulsations are often induced. This was shown by test results performed for systems with a single side branch and co-axial branches with the same lengths. With growing the flow velocity an excitation of successive resonant modes was observed. Their frequencies were increased together with the flow velocity but at peaks of sound pressure there was an excellent agreement between measurements results and theoretical predictions. A conversion of fluctuating flow energy to energy of resonant acoustic field was included in theoretical consideration by means of negative resistance in impedance model of branches. Hence, it was possible to predict a stronger nonlinearity in the case of a duct with co-axial branches. It was found that a characteristic parameter of the analyzed phenomenon is Strouhal number. Its values for all modes are within the same range approximately and, in addition, it determines a change of acoustic inertance at the branch opening.